Informed Consent for Intraoperative Neural Monitoring in Thyroid and Parathyroid Surgery – Consensus Statement of the International Neural Monitoring Study Group - Wu, Che-Wei; Huang, Tzu-Yen; Randolph, Gregory W.; Barczyński, Marcin; Schneider, Rick; Chiang, Feng-Yu; Silver Karcioglu, Amanda; Wojtczak, Beata; Frattini, Francesco; Gualniera, Patrizia; Sun, Hui; Weber, Frank; et al. (Frontiers in Endocrinology, 2021)
In the past decade, the use of intraoperative neural monitoring (IONM) in thyroid and parathyroid surgery has been widely accepted by surgeons as a useful technology for improving laryngeal nerve identification and voice outcomes, facilitating neurophysiological research, educating and training surgeons, and reducing surgical complications and malpractice litigation. Informing patients about IONM is not only good practice and helpful in promoting the efficient use of IONM resources, but is indispensable for effective shared decision making between the patient and surgeon. The International Neural Monitoring Study Group (INMSG) feels complete discussion of IONM in the preoperative planning and patient consent process is important in all patients undergoing thyroid and parathyroid surgery. The purpose of this publication is to evaluate the impact of IONM on the informed consent process before thyroid and parathyroid surgery and to review the current INMSG consensus on evidence-based consent. The objective of this consensus statement, which outlines general and specific considerations as well as recommended criteria for informed consent for the use of IONM, is to assist surgeons and patients in the processes of informed consent and shared decision making before thyroid and parathyroid surgery.